PENINGKATAN HASIL BELAJAR PASSING BAWAH BOLA VOLI DENGAN MODIFIKASI BOLA PLASTIK DI SDN - Jalimah, .; Haetami, Mimi; Triansyah, Andika (Jurnal Pendidikan dan Pembelajaran Khatulistiwa, 2017)
Abstract:The purpose of this research to determine the increase passing under volleyball with plastic balls modification learners fifth grade at SDN 33 Simpang Sanurian Landak. The method used in this research is descriptive method with this type of research is classroom action research. Subjects who made this study were teachers collaborate with learners class V SDN 33 Simpang Sanurian Landak as many as 20 students. The results of the first cycle of learning research students who completed amounted to 12 or 60%, while the students who have not passed or have not completed amounted to 8 or 40%, then proceed to the second cycle so that learners have an opportunity for improvement. In the second cycle students who graduated a total of 20 people or 100% and unresolved numbered 0 or does not exist.Keywords: Passing Down, Plastic Ball Modifications